Characterization of the laccase-mediated oligomerization of 4-hydroxybenzoic acid. Issue 101 (18th October 2016) - Slagman, Sjoerd; Escorihuela, Jorge; Zuilhof, Han; Franssen, Maurice C. R.
Abstract : The curious (lac)case of four dimers – how minor 4-hydroxybenzoic acid dimers can be of major importance. Abstract : Modifying inert poly(ethersulfone) membranes using laccase has proven to be an environmentally benign and easily applicable process to alter the membrane's surface properties. By this method phenolic acid monomers such as 4-hydroxybenzoic acid are grafted from the membrane surface to make it anti-fouling. In order to enhance the anti-fouling capabilities even further it is important to study the molecular details of this reaction. However, the nature of the products of laccase modification, either on a surface or in solution, has been studied only poorly. In this paper we report the formation of C3–C3′, C3–O and C1–C3′ linked dimers as the first products of the solution-phase laccase-mediated oligomerization of 4-hydroxybenzoic acid. These dimers can also act as substrate for laccase, and we show that their enzymatic oxidative coupling occurs far more rapidly than that of 4-hydroxybenzoic acid, which indicates that they are highly reactive intermediates that are efficiently polymerized onwards. The reactivity of each dimer is of large influence on its yield; dimers that are converted more rapidly are less abundant. This knowledge allows for further improvement of applications involving laccase such as the grafting of phenols on surfaces and enzymatic polymerization of lignin fragments.